Single‐Pump‐Actuated Transformable Dual‐Mode Gripper Based on Bistable and Origami Structures for Cross‐Scale Object Grasping - Tianle Pan; Jing Shu; Huayu Zhang; Shuhao Xia; Jinfei Hu; Jianshu Zhou; Yunhui Liu; Xin Ma (Advanced Intelligent Systems)
The manipulation of objects of varying sizes is crucial for grippers used in logistics and smart home applications. However, conventional grippers lack cross‐scale grasping capabilities. This study presents a novel single‐pump‐actuated transformable dual‐mode gripper (SATDG) that combines vacuum suction and granular jamming to effectively grasp objects ranging from 10 to 300 mm in size, covering a vast 30‐fold range, with forces from 0.5 to 21 N. Using a bistable mechanism and origami structure, the SATDG can transform between two modes and activate them with one pressure source. Subsequently, a finite‐element analysis of the characteristics of the bistable frame and the origami structure is presented. The performances of both grasping modes of the SATDG are validated. Demonstrations have shown that the SATDG performs outstandingly in logistics and smart home scenarios.